Integrated analysis of multiple microarray studies to establish differential diagnostic models of Crohn’s disease and ulcerative colitis based on a metalloproteinase-associated module - Deng, Jiang; Zhao, Ning; Lv, Li-ping; Ma, Ping; Zhang, Yang-yang; Xu, Jin-bo; Zhou, Xi-peng; Chen, Zi-an; Zhang, Yan-yu (Frontiers in Immunology, 2022)
Background: Ulcerative colitis (UC) and Crohn's disease (CD) subtypes of inflammatory bowel disease (IBD) are autoimmune diseases influenced by multiple complex factors. The clinical treatment strategies for UC and CD often differ, indicating the importance of improving the discrimination of the two. Methods: Two methods, robust rank aggregation (RRA) analysis and merging and intersection, were applied to integrate data from multiple IBD cohorts, and the identified differentially expressed genes (DEGs) were used to establish a protein‒protein interaction (PPI) network. Molecular complex detection (MCODE) was used to identify important gene sets. Two differential diagnostic models to distinguish CD and UC were established via least absolute shrinkage and selection operator (LASSO) logistic regression, and model evaluation was performed in both training and testing groups and included receiver operating characteristic (ROC) curves, calibration plots and decision curve analysis (DCA). The potential value of MMP-associated genes was further verified using different IBD cohorts and clinical samples. Results: Four datasets (GSE75214, GSE10616, GSE36807, GSE9686) were included in the analysis. Both data integration methods indicated that activation of the MMP-associated module was significantly elevated in UC. Two LASSO models based on continuous variable (Model_1) and binary variable (Model_2) MMP-associated genes were established to discriminate CD and UC. The results showed that Model_1 exhibited good discrimination in the training and testing groups. The calibration analysis and DCA showed that Model_ 1 exhibited good performance in the training group but failed in the testing group. Model_2 exhibited good discrimination, calibration and DCA results in the training and testing groups and exhibited greater diagnostic value. MMP genes exhibited high value as biomarkers for the discrimination of IBD patients using published cohort and immunohistochemistry (IHC) staining data. MMP-associated gene levels exhibited statistically significant positive correlations with levels of the differentially expressed cell types, indicating their potential value in differential diagnosis. Conclusion: MMP-associated modules are the main differential gene sets between CD and UC. The established Model_2 overcomes batch differences and has good clinical applicability. Subsequent in-depth research on how MMPs are involved in the development of different IBD subtypes is necessary.